The Gender Gap in Earnings Losses after Job Displacement - Hannah Illing; Johannes F. Schmieder; Simon Trenkle (Institute of Labor Economics (IZA), 2021)
Existing research has shown that job displacement leads to large and persistent earnings losses for men, but evidence for women is scarce. Using administrative data from Germany, we apply an event study design in combination with propensity score matching and a reweighting technique to directly compare men and women who are displaced from similar jobs and firms. Our results show that after a mass layoff, women's earnings losses are about 35% higher than men's, with the gap persisting five years after job displacement. This is partly explained by a higher propensity of women to take up part-time or marginal employment following job loss, but even full-time wage losses are almost 50% (or 5 percentage points) higher for women than for men. We then show that on the household level there is no evidence of an added worker effect, independent of the gender of the job loser. Finally, we document that parenthood magnifies the gender gap sharply: while fathers of young children have smaller earnings losses than men in general, mothers of young children have much larger earnings losses than other women.
Keywords: J63; J22; J23; J16; 330; household structure; labor supply; gender pay gap; job-loss